2015
DOI: 10.1371/journal.pone.0134245
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cardiac Troponin-I is Superior to Troponin-T as a Marker for Left Ventricular Dysfunction in Clinically Stable Patients with End-Stage Renal Disease

Abstract: BackgroundSerum troponin assays, widely used to detect acute cardiac ischemia, might be useful biomarkers to detect chronic cardiovascular disease (CVD). Cardiac-specific troponin-I (cTnI) and troponin-T (cTnT) generally detect myocardial necrosis equally well. In dialysis patients however, serum cTnT levels are often elevated, unlike cTnI levels. The present study aims to elucidate the associations of cTnI and cTnT with CVD in clinically stable dialysis patients.MethodsTroponin levels were measured using 5th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
2
26
1
Order By: Relevance
“…Where it has been reported, in the Implantable Cardioverter Defibrillators in Dialysis patients (ICD2) Trial, RRF correlated negatively with hs-TnT. 15 Levels of other biomarkers were not reported in this study. We also assessed residual kidney function as daily urine volume, a more practical method in practice.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Where it has been reported, in the Implantable Cardioverter Defibrillators in Dialysis patients (ICD2) Trial, RRF correlated negatively with hs-TnT. 15 Levels of other biomarkers were not reported in this study. We also assessed residual kidney function as daily urine volume, a more practical method in practice.…”
Section: Discussioncontrasting
confidence: 51%
“…12,13 The plasma concentrations of cardiac troponins I and T are frequently elevated in haemodialysis patients due to cardiac factors and/or dialysis-related factors. 14,15 Regardless of the reason, elevated cardiac troponin in haemodialysis patients is associated with adverse outcomes. 16,17 We aimed to determine how measures of cardiac structure and function assessed by echocardiography and measures of residual kidney function were associated with levels of these biochemical markers of cardiac disease in haemodialysis patients.…”
mentioning
confidence: 99%
“…Studies have reported that haemodialysis may reduce hs-cTnT levels by at least 10%, and in some cases up to 50%, in stable patients with ESRD, which suggest at least a partial renal clearance of cTnT (99,100). The magnitude of elevated hs-cTnT levels observed with declining renal function seem to be more pronounced than that for hs-cTnI levels (55), and hs-cTnT levels are higher in patients ESRD (101). Intact cTnT has a molecular weight of 37 kDa, which suggest a low degree of filtration through the glomerular membrane.…”
Section: Chronic Myocardial Injury and Renal Functionmentioning
confidence: 96%
“…Cardiac troponin T and I are the proteins in actin filaments that regulate the speed and force of contraction in cardiac cells. These are highly specific and sensitive markers for cardiac cell damage, and are extensively released into blood plasma following cardiac damage or fatigue (9,10). CTn-T, cTn-I, creatine kinase (CK) and its iso-enzyme (CK-MB) are appropriate tools for diagnosis of damage to cardiac muscle cells, ischemia, and cardiac muscle infarction (11).…”
Section: Introductionmentioning
confidence: 99%